First Evidence of Miocene Avian Tracks from Sumatra: Short Announcement - Yahdi Zaim; Yan Rizal; Gregg F. Gunnell; Thomas A. Stidham; Russell L. Ciochon; Aswan Aswan (Ikatan Ahli Geologi Indonesia, 2011)
-